MENINGKATKAN MATEMATIKA DASAR PADA ANAK USIA DINI DI TK SELUSAKA KABUPATEN SERAM BAGIAN BARAT DENGAN PEMANFAATAN BUAH LASA - Gayatri Lessy; Marissa Irmuply; Sarah Supulatu; Julenda Gorangamury (Nusantara Hasana Journal, 2026)
The low basic mathematics ability of children aged 4–5 years at TK Selusaka, West Seram Regency, is characterized by the inability to count in the correct sequence, failure to identify numbers accurately, and insufficient recognition of geometric shapes due to a lack of teaching aids. This study aims to describe and analyze efforts to improve early childhood basic mathematics ability through the utilization of lasa fruit (Castanopsis buruana Miq) as an innovative teaching aid based on local natural resources. A descriptive qualitative approach was employed, with data collected through participant observation, in-depth interviews with classroom teachers and the school principal, and documentation. The research subjects were 16 students aged 4–5 years at TK Selusaka. The study was conducted from May 9 to June 9, 2025, preceded by a one-week teacher training on making lasa-based teaching aids (May 19–23, 2025). Results indicate that the use of lasa fruit significantly improved children's basic mathematics ability, including: (1) recognition of numbers 1–10, with 7 out of 16 children beginning to write numerals; (2) sequential counting ability 1–10 improved in 10 out of 16 children; (3) understanding of simple addition and subtraction; and (4) recognition and grouping of geometric shapes. Use of lasa fruit also increased children's motivation, enthusiasm, and active participation. Challenges included the limited durability of organic material, hygiene concerns, and natural variation in fruit size. This study concludes that local natural resources such as lasa fruit have great potential as effective, economical, and contextual mathematics learning media for early childhood.